Exercise and physical activity recommendations for people with cerebral palsy. (7th February 2016) - Verschuren, Olaf; Peterson, Mark D; Balemans, Astrid C J; Hurvitz, Edward A
Abstract : Physical activity and its promotion, as well as the avoidance of sedentary behaviour, play important roles in health promotion and prevention of lifestyle‐related diseases. Guidelines for young people and adults with typical development are available from the World Health Organisation and American College of Sports Medicine. However, detailed recommendations for physical activity and sedentary behaviour have not been established for children, adolescents, and adults with cerebral palsy (CP). This paper presents the first CP‐specific physical activity and exercise recommendations. The recommendations are based on (1) a comprehensive review and analysis of the literature, (2) expert opinion, and (3) extensive clinical experience. The evidence supporting these recommendations is based on randomized controlled trials and observational studies involving children, adolescents, and adults with CP, and buttressed by the previous guidelines for the general population. These recommendations may be used to guide healthcare providers on exercise and daily physical activity prescription for individuals with CP. What this paper adds: This paper provides an overview of intervention studies including cardiorespiratory endurance training and muscle strengthening for individuals with cerebral palsy (CP). This paper includes prescription guidelines pertaining to volume, intensity, and duration of physical activity and exercise for individuals with CP. We present the first CP‐specific, evidence‐based physical activity, and exercise recommendations, which may be incorporated into a clinical setting. This article is commented on by Wiart on page788 of this issue.